'Barrier dysfunction in Atopic newBorns studY' (BABY): protocol of a Danish prospective birth cohort study. Issue 7 (12th July 2020) - Gerner, Trine; Halling, Anne-Sofie; Rasmussen Rinnov, Maria; Haarup Ravn, Nina; Hjorslev Knudgaard, Mette; Menné Bonefeld, Charlotte; Ewertsen, Caroline; Trautner, Simon; Jakaša, Ivone; Kezic, Sanja; Skov, Lone; Thyssen, Jacob P
Abstract : Introduction: Skin barrier development and dysfunction in premature and mature newborns is important for the risk of atopic dermatitis (AD). Methods and analysis: The Barrier dysfunction in Atopic newBorns studY (BABY) Cohort is a prospective birth cohort study of 150 preterm children (gestational age (GA) below 37+0) and 300 term children (GA 37+0 to 41+6). Skin barrier is assessed through transepidermal water loss, tape stripping, Raman-spectroscopy and microbiome sampling. Clinical examinations are done and DNA from buccal swabs is collected for genetic analyses. Thymus size is assessed by ultrasound examination. Information on pregnancy, delivery, parental exposures and diseases are collected, and structured telephone interviews are conducted at 18 and 24 months to assess exogenous exposures in the child and onset of AD. Hanifin and Rajka criteria as well as The UK Working Party's Diagnostic Criteria for Atopic Dermatitis are used to diagnose AD. Severity of AD is assessed using the Eczema Area and Severity Index (EASI) and Patient Oriented Eczema Measure (POEM). Ethics and dissemination: The study is approved by the scientific Ethical Committee of the Capital Region (H-16042289 and H-16042294). Outcomes will be presented at national and international conferences and in peer-reviewed publications.